An analysis of determinants of deposit money banks lending in Nigeria, 1990-2014 - Biwet Mwanret Inusa (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2018)
Deposit money banks thrives on financial intermediation. Funds lending constitutes the largest income-earning asset in the portfolio of most deposit money banks generally. Hence, banks deploy huge resources to estimate, monitor and manage the quality of their loans and advances. This study aims at investigating the determinants of lending of deposit money banks in Nigeria. Secondary data was used to justify the relationship between commercial banks and lending in Nigeria. More so, the model used was estimated using Nigeria deposit money banks loans and advances (LOA) as dependent variable, and determinants (independent variables) such as volume of deposit (Vd), Interest rate (Ir), liquidity ratio (Lr) and annual average exchange rate (ExR) for the period of 1990 - 2014 (25 years). The techniques used in this investigation were : Augmented Dickey-fuller (ADF) test), multiple regression analysis and Granger causality test. The estimated result revealed that there is a positive relationship between loans and advances and volume of deposit and annual average exchange rate of Naira to dollar, while interest rate and liquidity ratio has a negative relation: all conform to the approri expectation. The study then suggests that commercial banks should focus on mobilizing more deposits as this will enhance their lending performance, and should formulate critical, realistic and functional plans that will ensure its profitability, liquidity and solvency. The government should ensure it uses monetary policy such that will create enabling environment for the deposit money banks to generate more deposits so as to channel it to investors for investment